Technician teaming and routing with service-, cost- and fairness-objectives. (September 2019) - Anoshkina, Yulia; Meisel, Frank
Highlights: We investigate a combined problem of creating and routing worker groups (teams). We consider various goals expressing service-, fairness- and cost-objectives. We present an optimization model and provide a bi-level decomposition scheme. We show by experiment the importance of employee qualification for solution quality. Abstract: In workforce routing and scheduling there are many applications in which differently skilled workers must perform jobs that occur at different locations, where each job requires a particular combination of skills. In many such applications, a group of workers must be sent out to provide all skills required by a job. Examples are found in maintenance operations, the construction sector, health care operations, or consultancies. In this paper, we analyze the combined problem of composing worker groups (teams) and routing these teams under goals expressing service-, fairness-, and cost-objectives. We develop mathematical optimization models for an integrated solution and a sequential solution of the teaming- and routing-subproblems. Computational experiments are conducted to identify the tradeoff of better solution quality and computational effort that comes along with solving the subproblems within a combined monolithic model and within bi-level decomposition schemes. We further analyze the impact of the qualification of employees on the different objectives.